2018
DOI: 10.1111/irv.12558
|View full text |Cite
|
Sign up to set email alerts
|

The potential economic value of influenza vaccination for healthcare workers in The Netherlands

Abstract: BackgroundDespite the clinical evidence, influenza vaccination coverage of healthcare workers remains low. To assess the health economic value of implementing an influenza immunization program among healthcare workers (HCW) in University Medical Centers (UMCs) in the Netherlands, a cost‐benefit model was developed using a societal perspective.Methods/PatientsThe model was based on a trial performed among all UMCs in the Netherlands that included both hospital staff and patients admitted to the pediatrics and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The majority of the evaluated studies reported their outcomes using CUA [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Other types of economic evaluation considered were CEAs ( N = 11) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], CBA (11 studies) [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], or combining more than one type (10 studies) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the evaluated studies reported their outcomes using CUA [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Other types of economic evaluation considered were CEAs ( N = 11) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], CBA (11 studies) [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], or combining more than one type (10 studies) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reflected the societal perspective ( N = 18) [ 30 , 34 , 35 , 36 , 41 , 42 , 43 , 45 , 46 , 47 , 55 , 57 , 63 , 64 , 67 , 73 , 78 , 79 ]. Fifteen studies evaluated the issue in question from more than one perspective, combining the societal perspective with another perspective [ 27 , 32 , 33 , 37 , 38 , 39 , 40 , 44 , 49 , 52 , 56 , 59 , 66 , 68 , 77 ]. The rest of the studies considered either a healthcare provider perspective [ 29 , 31 , 50 , 58 , 72 , 75 ], employer perspective [ 60 , 65 ], patient perspective [ 51 ], family perspective [ 69 ], school perspective [ 70 ], net monetary benefit perspective [ 71 ], or medical insurance perspective [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations